DRABETS SEMIOTIK: Eksempler fra krigen i Algeriet 1954-1962 - Boserup, Rasmus Alenius (Tidsskriftet Antropologi, 2018)
This article analyses the ways in which the paramilitary group FLN-ALN used to kill its enemies in the French and the Muslim populations during the Algerian “War of Independence” from 1954-1962. Through empirical material from classified French military archives the article demonstrates that the FLN-ALN’s methods of killing their French enemies differed from the way they killed their Muslim enemies. Based on this observation, it is argued that FLN-ALN’s war, in fact, consisted of two separate wars: An external war with the objective of establishing an independent Algerian state and an internal war with the objective of creating a “liberated” Algerian society. These two wars were not only fought against different enemies but also were conceptualized differently. FLN-ALN transformed the two wars into radically different forms and methods of physical violence and killing. Hence, the central argument of the article is that forms of violence are signs, as understood in semiotic analysis, and that FLN-ALN used the physical treatment of the two enemies’ bodies to communicate with friendly and opposed political communities both inand outside of Algeria